Ageing in Rett syndrome. (16th September 2015) - Cianfaglione, R.; Clarke, A.; Kerr, M.; Hastings, R. P.; Oliver, C.; Felce, D.
Abstract: Background: The aim was to gain a UK national sample of people with Rett syndrome across the age range and (1) conduct a cross‐sectional comparison of age groups and (2) undertake a longitudinal follow‐up. Methods: From 308 potential participants approached to take part, a sample of 91 girls and women was achieved (29.5%). Their ages ranged from 4 to 47 years, and 71 were known to have a mutation in the methyl‐CpG binding protein‐2 ( MECP2 ) gene. Seventy‐two of the initial sample were followed up 16 months later, and 50 returned completed assessments (69.4%). Their ages ranged from 7 to 48 years, and 42 were MECP2 positive. Parental questionnaire measures of Rett syndrome specific characteristics, impulsivity, overactivity, mood, interest and pleasure, repetitive behaviour and self‐injury were administered. Results: Adaptive behaviour and behavioural characteristics of Rett syndrome were similar across age groups and, where assessed, stable over time, as were repetitive behaviours generally and self‐injury. There was some suggestion of deterioration in health arising with ageing, principally contributed to by deteriorations in dental and gastro‐intestinal problems both with moderate effect sizes. Indicators of mood, interest and pleasure differed significantly across age groups. The total scale score significantly deteriorated over time, with a moderate effect size. Conclusions: This study provides further evidence for the post‐regression stability that characterises Rett syndrome. Emergent low mood in Rett syndrome requires further research.